Collaborative agreements: A ‘how to’ guide - Henson-Apollonio, V. (2005)
Partnerships can be an extremely effective way to harness additional skills and resources and minimize costs. Collaboration allows scientists (and other partners) to access a broad range of expertise and fosters a multi-disciplinary approach, both of which are often required when tackling complex research issues. However, it may be difficult to make the most of collaborative agreements, since different partners may have different objectives and approaches and misunderstandings can occur.